The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1200/jco.2021.39.3_suppl.268
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab (pembro) vs placebo (pbo) in patients (pts) with advanced hepatocellular carcinoma (aHCC) previously treated with sorafenib: Updated data from the randomized, phase III KEYNOTE-240 study.

Abstract: 268 Background: KEYNOTE-240 (NCT02702401) examined the anti-PD-1 antibody pembro and demonstrated improvement in OS and PFS vs pbo in pts with aHCC previously treated with sorafenib. However, the study did not meet prespecified statistical significance criteria for OS and PFS. Median OS (final analysis) was 13.9 mo for pembro vs 10.6 mo for pbo (HR 0.781; 95% CI 0.611-0.998). At the first interim analysis when PFS and ORR were prespecified to be tested, median PFS was 3.0 mo for pembro vs 2.8 mo for pbo (HR 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…246 Updated data from the KEYNOTE-240 trial, published in an abstract, showed that the median OS with pembrolizumab versus placebo was 13.9 vs 10.6 months, respectively (HR, 0.77) and the median PFS was 3.3 vs 2.8 months, respectively (HR, 0.70). 247 Also, a clinically meaningful difference in ORR was seen favoring pembrolizumab (18.3% vs 4.4%), and the median duration of response on pembrolizumab was 13.9 months. Pembrolizumab has maintained its accelerated approval in patients previously treated with sorafenib.…”
Section: Subsequent-line Therapy If Disease Progressionmentioning
confidence: 88%
“…246 Updated data from the KEYNOTE-240 trial, published in an abstract, showed that the median OS with pembrolizumab versus placebo was 13.9 vs 10.6 months, respectively (HR, 0.77) and the median PFS was 3.3 vs 2.8 months, respectively (HR, 0.70). 247 Also, a clinically meaningful difference in ORR was seen favoring pembrolizumab (18.3% vs 4.4%), and the median duration of response on pembrolizumab was 13.9 months. Pembrolizumab has maintained its accelerated approval in patients previously treated with sorafenib.…”
Section: Subsequent-line Therapy If Disease Progressionmentioning
confidence: 88%
“…Finally, 57 records (representing 50 trials) were included in the SLR. These 50 trials included 34 trials in the 1L setting (six single arm [30][31][32][33][34][35], six RCTs comparing against a recommended treatment or placebo [36][37][38][39][40][41][42][43], one trial with both single arm and randomized groups [44], and 26 RCTs comparing against a non-recommended treatment ) and 11 trials in the 2L setting (five single arm [71][72][73][74][75][76], five RCTs comparing against placebo [77][78][79][80][81][82], and one trial with both single arm and randomized groups [83][84][85][86]).…”
Section: Resultsmentioning
confidence: 99%
“…Last, the comparison of atezolizumab + bevacizumab versus atezolizumab alone found an improvement in PFS, but OS was not reported ( Figure 4 ) [ 44 ]. In the 2L setting, cabozantinib and regorafenib were associated with significant improvements in PFS and OS over placebo [ 77 , 79 ]; results for ramucirumab were mixed [ 78 , 80 ], and pembrolizumab did not significantly lower PFS and OS per the trial's specified criteria [ 81 , 82 ] ( Supplementary Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, the FDA granted accelerated approval for the use of pembrolizumab in patients progressing on sorafenib. Another phase III trial comparing pembrolizumab to placebo in the second-line treatment of advanced HCC did not meet its primary endpoints (OS and PFS) based on the rigorous statistical plan [75]. The combination of lenvantanib, an inhibitor of vascular endothelial growth factor receptor (VEGFR), of fibroblast growth factor receptor, of platelet-derived growth factor receptor (PDGFR), and other growth signaling kinases, and pembrolizumab was assessed in the phase Ib trial of 104 patients with unresectable HCC [76].…”
Section: Immunotherapy For Hccmentioning
confidence: 99%